EEG/MEG Propagating Dipole Source Estimation - Bria, Oscar N. (2001)
Electroencephalography (EEG) and magnetoencephalography (MEG) are the only two methods to study the functional organization of the brain with a temporal resolution close to 1 ms. This unique feature seems to be useful to measure with enough precision propagating activity on the cortex. Moreover, both EEG and MEG are complementary rather than competitive, as mathematically argued by Muravchik and Nehorai in [9]. An example of application of brain topography is the treatment of patients suffering from temporal lobe epilepsy (TLE), in which anti-epileptic drug treatment fails. Seizures, with loss of conscience, may occur in such patients several times a month or even many times a day, and thus severely hamper social functioning. These patients can be considered candidates for surgery. When considering surgery, it is important that the location of the epileptic focus is well determined beforehand.